Buddhism and modernity sources from nineteenth-century Japan - Klautau, Orion 1980-; Krämer, Hans Martin 1972- (Honolulu University of Hawaii Press, 2021)
Questions and Answers from Beneath a Snowy Window (1876) by Fukuda Gyōkai / Micah Auerback -- On Religious Revolution (1889) by Nakanishi Ushirō / Hoshino Seiji -- Fraternity of Puritan Buddhists: Our Manifesto (1900) by Anonymous / Jolyon Baraka Thomas -- Discussing the Kanrenkai (1897) by Kyōkai Jigensha (attrib. Kiyozawa Manshi) / Jeff Schroeder -- On Protecting the Nation through Buddhism (1856) by Gesshō / Orion Klautau -- Upholding Faith in the Buddhadharma and Repaying the Nation (1863) by Ogawa Taidō / Jacqueline I. Stone -- Lectures on the Three Articles of Instruction (1873) by Higuchi Ryūon / Hans Martin Krämer -- Laughing at Christianity (1869) by Kiyū Dōjin / James Baskind -- On the National Doctrine of Greater Japan (1882) by Shaku Unshō / Kameyama Mitsuhiro and Nathaniel Gallant -- A Buddhist Book of Genesis (1879) by Sada Kaiseki / Fabio Rambelli -- The Gist of Indian Philosophy (1887) by Hara Tanzan / Dylan Luers Toda -- Prolegomena to an Argument for the Revival of Buddhism (1887) by Inoue Enryō / Jason Ā. Josephson-Storm -- Discourse on Buddhist Unity (1901) by Murakami Senshō / Ryan Ward -- On Civilization (1876) by Ōuchi Seiran / Orion Klautau -- Publishing Goals of Hanseikai zasshi (1887) and Living the Pure Life (1887) by Hanseikai zasshi / James Mark Shields -- On the Relationship Between Man and Woman (1888) by Shimaji Mokurai / Iwata Mami and Stephan Kigensan Licha -- On Buddhist Marriage (1894) by Tanaka Chigaku / G. Clinton Godart -- The Problem of Faith (1904) by Chikazumi Jōkan / Garrett L. Washington -- A Plan to Protect the Dharma (1874/1903) by Ogurusu Kōchō / Erik Schicketanz -- A Record of Niuzhuang (1895) by Yamagata Genjō / Micah Auerback -- The Japanese People's Spirit (1912) by Shaku Sōen / Michel Mohr -- A Travelogue in Tibet (1904) by Kawaguchi Ekai / Nathaniel Gallant
"Japan was the first Asian nation to face the full impact of modernity. Like the rest of Japanese society, Buddhist institutions, individuals, and thought were drawn into the dynamics of confronting the modern age. Japanese Buddhism had to face multiple challenges, but it also contributed to modern Japanese society in numerous ways. Buddhism and Modernity: Sources from Nineteenth-Century Japan makes accessible the voices of Japanese Buddhists during the early phase of high modernity. The volume offers original translations of key texts-many available for the first time in English-by central actors in Japan's transition to the modern era, including the works of Inoue Enryō, Gesshō, Hara Tanzan, Shimaji Mokurai, Kiyozawa Manshi, Murakami Senshō, Tanaka Chigaku, and Shaku Sōen. All of these writers are well recognized by Buddhist studies scholars and Japanese historians but have drawn little attention elsewhere; this stands in marked contrast to the reception of Japanese Buddhism since D. T. Suzuki, the towering figure of Japanese Zen in the first half of the twentieth century. The present book fills the chronological gap between the premodern era and the twentieth century by focusing on the crucial transition period of the nineteenth century. Issues central to the interaction of Japanese Buddhism with modernity inform the five major parts of the work: sectarian reform, the nation, science and philosophy, social reform, and Japan and Asia. Throughout the chapters, the globally entangled dimension-both in relation to the West, especially the direct and indirect impact of Christianity, and to Buddhist Asia-is of great importance. The Introduction emphasizes not only how Japanese Buddhism was part of a broader, globally shared reaction of religions to the specific challenges of modernity, but also goes into great detail in laying out the specifics of the Japanese case"--
2103
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Buddhism -- Japan -- History -- 19th century -- Sources -- Translations into English; Buddhism -- History -- 1600-1868 -- Japan; Buddhism -- History -- 1868-1945 -- Japan